Diversivikasi Produk dan Pemasaran Berbasis IT untuk Meningkatkan Nilai Tambah Omzet Penjualan UMKM Tempe Bagong - Rusno, Rusno; Putra, Dwi Fauzia; Susanto, Gaguk; Kusufa, Roni Alim Ba’diya; Firdaus, Riril Mardiana; Fakih, Abdul; Ningrum, Putri Setyo (STIE Malangkucecwara, 2024)
Tempe Bagong UMKM is a business engaged in processing soybeans into traditional tempeh. The problems that occur in Tempe Bagong UMKM Partners include not having other tempeh product variations, tempeh bagong product packaging is still absent, and the marketing process is still being sold in small stalls around the village. The community service approach method used to help partner problems is Participatory Learning and Action (PLA). The steps of the Participatory Learning and Action (PLA) approach are characterized by socialization, discussion, and direct training practices. The stages of this community service activity are pre-training, education stage, practice stage, mentoring stage, and evaluation stage. Through this community service, diversification is produced in the form of tempeh bungkil which is a mixture of soybeans, soybean skin, copra, and peanuts. This product is packaged more attractively to increase its selling value. In addition, digital marketing is also carried out through digital marketing